2012
DOI: 10.1002/dmrr.2306
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of heat shock protein 60 epitopes in children with type 1 diabetes

Abstract: Background Treatment with a specific HSP60 epitope in new onset of type 1 diabetes (T1D) patients has been shown to preserve endogenous insulin production. Previously, recognition of pan HLA‐DR‐binding HSP60 epitopes in various autoimmune diseases was found; this study investigated recognition of these epitopes in newly diagnosed T1D patients and correlated findings to the occurrence of a partial remission. Methods Peripheral blood mononuclear cells of 18 children with T1D were prospectively collected at disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Various studies with human patients have shown that treatment of Type 1 diabetes with p277 epitope can preserve part of the endogenous insulin production by arresting the destruction of the β -cell mass in the pancreas [ 25 , 26 ]. The paper by Stuart et al, 2012, states that a number of Hsp60 peptide epitopes that can bind multiple allelic variants of the human major histocompatibility complex molecule HLA-DR are called pan-DR epitopes which can induce low peptide-specific proliferative responses and peptide-specific production of intracellular cytokines such as interleukin-10 (IL-10), an anti-inflammatory cytokine, and interferon- γ (IFN- γ ) in Type 1 diabetes [ 26 ]. This suggests that Hsp60 and peptides derived from the full-length molecule can induce both proinflammatory and anti-inflammatory cytokines.…”
Section: Role Of Mitochondrial Hsp60 In Types 1 and 2 Diabetes Melmentioning
confidence: 99%
“…Various studies with human patients have shown that treatment of Type 1 diabetes with p277 epitope can preserve part of the endogenous insulin production by arresting the destruction of the β -cell mass in the pancreas [ 25 , 26 ]. The paper by Stuart et al, 2012, states that a number of Hsp60 peptide epitopes that can bind multiple allelic variants of the human major histocompatibility complex molecule HLA-DR are called pan-DR epitopes which can induce low peptide-specific proliferative responses and peptide-specific production of intracellular cytokines such as interleukin-10 (IL-10), an anti-inflammatory cytokine, and interferon- γ (IFN- γ ) in Type 1 diabetes [ 26 ]. This suggests that Hsp60 and peptides derived from the full-length molecule can induce both proinflammatory and anti-inflammatory cytokines.…”
Section: Role Of Mitochondrial Hsp60 In Types 1 and 2 Diabetes Melmentioning
confidence: 99%
“…The research to date on HSPs in the field of diabetes has limitations. A study reporting T-cell proliferative responses and HSP60-derived epitope-specific cytokine production should be interpreted with caution as patient numbers were small ( 111 ). Genetic polymorphism in HSP genes also present a confounding factor for interpretation of both pre-clinical and clinical data in HSPs-T1D studies.…”
Section: Limitations Of the Hsp Studies In Diabetes Researchmentioning
confidence: 99%